Земський лібералізм північної України (60–80 рр. ХІХ ст.): витоки та програматика - Котельницький, Н.А. (Сіверщина в історії України, 2021)
Стаття присвячена дослідженню витоків та програмати-
ки земського ліберального руху на півночі Лівобережної України(60–80 рр. ХІХ ст.). У лаконічній формі висвітлені основні джерела та історіософські імперативи, які кристалізували головні
параметри загальної політичної програми опозиційної аристократичної фронди північної України. Автор приходить до висновків про те, що земський ліберальних рух на півночі Лівобережної
України є вельми цікавим явищем української історії ХІХ ст., яке
й досі залишається «білою плямою» вітчизняної історіографії. The article is devoted to the study of the origins and programs of the
zemstvo liberal movement in the north of the Left Bank of Ukraine (60-80s
of the XIX century). The main sources and historiosophical imperatives,
which crystallized the main parameters of the general political program
of the opposition aristocratic front of northern Ukraine, are highlighted in
a concise form. The author concludes that the Zemstvo liberal movement
in the north of the Left Bank of Ukraine is a very interesting phenomenon
in the Ukrainian history of the XIX century, which still remains a «white
spot» of domestic historiography. The main sources of opposition in the
liberation movement of the Russian Empire were the Zemstvo reform of
1864; the young generation of university graduates brought up on democratic
ideals and the philosophical doctrine of liberalism; a conglomeration of the
Ukrainian national aristocracy, the opposition cosmopolitan nobility and
liberal populism. The origin of the absolute majority of the personal members
of the Zemstvo Liberal Party of Northern Ukraine from the community of
descendants of Ukrainian Cossack officers led to a fundamental diff erence
between the opposition front and its counterparts in the Zemstvo provinces
of the Russian Empire. The programmatic principles of the Zemstvo
liberalism of the Northern Left Bank at the initial stage of formation did
not go beyond the declared at the imperial level imperatives of this trend
in the liberation movement of the Russian Empire in the second half of the
nineteenth century: the adoption of the Constitution. , decentralization
of local self-government, elimination of arbitrariness of bureaucracy and
power structures, carrying out deep social and economic reforms.